Implementation of Parate Executie Based on Article 6 of Law Number 4 of 1996 concerning Guarantee of Dependent Rights to the Auction of Objects of Dependent Rights - Sunita Caroline Pontoh; M. Sudirman (Syntax Idea)
In general, there are laws that provide protection to banks as lenders to obtain repayment of their debts when the debtor is in default, this is stated in Article 1131 of the Civil Code which reads: "All assets of the Debtor, whether movable or immovable, whether existing ones or those that will be in the future become dependents/guarantees. Debtor's assets, both movable and immovable, both present and future will become dependents/guarantee for their debts”. Then Law Number 4 of 1996 was born which specifically regulates the implementation of Mortgage (UUHT). One of the characteristics of the UUHT is that it is easy and certain to execute, which means executing the mortgage certificate. must be carried out but can still provide legal certainty for interested parties, in this case, the auction seller, auction buyer and auctioneer. Therefore, in carrying out executions based on parate execution, it must be able to provide convenience and legal certainty for all interested parties